Accounting for climate transition risk in banks' capital requirements - Lucia Alessi; Erica Francesca Di Girolamo; Andrea Pagano; Marco Petracco Giudici (European Commission, 2022)
This paper uses a stylized simulation model to assess the potential impact of transition risk on banks' balance sheets and establishes a basis for calibrating relevant macro-prudential instruments. We show that even in the short run, a fire-sale mechanism could amplify an initially contained shock on highcarbon assets into a systemic crisis with significant losses for the EU banking sector. We calculate that an additional capital buer of 0.5% RWA on average would be sucient to protect the system. Moreover, under an orderly transition, the decrease in banks' transition risk exposure due to the greening of the economy would reduce the eect of a fire-sale by a factor of 10.
Keywords: C15; G2; Q54; 330; Green transition risk; dynamic balance sheet; banking crisis